Dynamical trade-offs arise from antagonistic coevolution and decrease intraspecific diversity - Weini Huang (Nature Portfolio, 2017)
How a trait evolves depends on the shape of its fitness trade-off. Here, Huang et al. demonstrate evolution of trade-off shape in an experimental predator-prey system and develop a mathematical model of trait evolution when the underlying trade-off can also evolve.